Hillforts and Defended Enclosures of the Welsh Borderland - W.J. Britnell; R.J. Silvester (Internet Archaeology, 2018)
Hillforts and defended enclosures are among the earliest and most enduring landmarks in the landscape of the Welsh borderland region and are vital to our understanding of its social and economic history for a millennium and a half, from the Late Bronze Age through to the early post-Roman period. Since the modern political map clearly is of no significance for this period, this review — which stems from recent survey and assessment work on hillforts and defended enclosures in central and north-east Wales — takes the opportunity to look across the border and see what is happening in the adjacent areas of England at this time.